Neuroligin 1 modulates striatal glutamatergic neurotransmission in a pathway and NMDAR subunit-specific manner - Espinosa, Felipe; Xuan, Zhong; Liu, Shunan; Powell, Craig M. (Frontiers in Synaptic Neuroscience, 2015)
ABSTRACT Together with its presynaptic partner Neurexin 1 (Nxn1), Neuroligin 1 (NL1) participates in synapse specification and synapse maintenance. We and others have shown that NL1 can also modulate glutamatergic synaptic function in the central nervous system of rodent models. These molecular/cellular changes can translate into altered animal behaviors that are thought to be analogous to symptomatology of neuropsychiatric disorders. For example, in dorsal striatum of NL1 deletion mice, we previously reported that the ratio N-methyl-D-aspartate receptor (NMDAR) mediated synaptic currents to α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor (AMPAR) mediated synaptic currents (NMDA/AMPA) is reduced in medium spiny neurons. Importantly, this reduction in NMDA/AMPA ratio correlated with increased repetitive grooming. The striatum is the input nucleus of the basal ganglia. Classical models of this circuitry imply that there are two principal pathways that render distinct and somewhat opposite striatal outputs critical to the function of these nuclei in modulating motor behavior. Thus, we set out to better characterize the effects of NL1 deletion on direct and indirect pathways of the dorsal striatum by genetically labeling medium spiny neurons participating in the direct and indirect pathways. We demonstrate that a decrease in NMDAR-mediated currents is limited to medium spiny neurons of the direct pathway. Furthermore, the decrease in NMDAR-mediated currents is largely due to a reduction in function of NMDARs containing the GluN2A subunit. In contrast, indirect pathway medium spiny neurons in NL1 KO mice showed a reduction in the frequency of miniature excitatory neurotransmission not observed in the direct pathway. Thus, NL1 deletion differentially affects direct and indirect pathway medium spiny neurons in dorsal striatum. These findings have potential implications for striatal function in NL1 KO mice.